Solitary Rectal Ulcer: A Literature Review - Bita Geramizadeh (Shiraz University of Medical Sciences, 2015)
Context Solitary rectal ulcer (SRU) is a disease with many challenging issues. There are several controversies about the basic pathophysiology of this disease. Despite its name, “solitary rectal ulcer”, more than a quarter of patients do not show any ulcer in colonoscopy. Instead, many patients show multiple polypoid lesions. Some previous reports have suggested calling this disease “rectal mucosal prolapse” instead of SRU, however, most of the patients do not have mucosal prolapse. In addition, colonoscopic findings can be very similar to cancer and inflammatory bowel disease, so without histologic evaluation, accurate diagnosis is not always possible. In patients with SRU, sometimes the rectal mucosa is so fibrotic that mucosal biopsy is inadequate, and even a pathologist cannot diagnose the characteristic histologic findings. There are various therapeutic approaches for the treatment of SRU, both surgical and nonsurgical, all of which are not optimal, and recurrence rates are still high with many patients experiencing complications even after surgery, resection and rectopexy. Evidence Acquisition Although this disease is not uncommon in Iran, there are very few studies from Iran, therefore, in this review we will describe our experience with patients with SRU in affiliated hospitals of Shiraz University of Medical Sciences. We will also review previously published articles about SRU that are indexed in PubMed and Google scholar, emphasizing the challenging issues. Results SRU is not an uncommon disease in Iran, however the number of published articles about it, is very low. Multicentric studies are necessary to find out the definite reason of this issue. Conclusions There are still many conflicting controversies about the etiology, pathogenesis, diagnosis and also treatment of SRU, which need further investigation and longer follow up of the patient in each therapeutic approach to be better understood.